Gas Chromatography - Mass Spectrometry Analysis of Hydroalcoholic Extract of Senna Siamea Lam Leaves - Ponmadasaamy.M; Akash. S; Abinesh. E; Jeeva. S; Kalairaj. M; Yogaraj. D; Vigneshwaran L.V (International Journal of Pharmacy and Analytical Research, 2026)
The present study was undertaken to identify the phytochemical constituents present in the hydroalcoholic extract of Senna siamea Lam. leaves using Gas Chromatography–Mass Spectrometry (GC–MS) analysis. Senna siamea, belonging to the family Fabaceae, is widely used in traditional medicine for the treatment of various ailments such as fever, microbial infections, diabetes, and inflammatory disorders. In this study, the leaves were collected, shade dried, powdered, and extracted using a hydroalcoholic solvent through the maceration method. The prepared extract was subjected to GC–MS analysis to determine the presence of volatile and semi-volatile bioactive compounds. The chromatographic results revealed the presence of six major phytochemical constituents including aromatic compounds, steroid derivatives, heterocyclic compounds, and phenolic acid derivatives. These compounds are known to exhibit important biological activities such as antimicrobial, antioxidant, anti-inflammatory, and hormonal effects. The findings support the medicinal significance of Senna siamea and indicate that the plant could be a promising source of bioactive molecules for future pharmacological and pharmaceutical research.